DESIGN INNOVATION IN ADVERTISING OF CAKRAWALA SPARKLING NATURE RESTAURANT AS ENTREPRENEURSHIP CREATIVITY FOR CUSTOMERS’ SATISFACTION - Dewi Untari; Lia Kurniawati; Muhammad Irsyad Raspati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Culinary Business continue to grow significantly. The growth can be seen in the emerging of cafes, restaurants, diners, and other eateries. One of many culinary business in Bandung is Cakrawala Sparkling Nature Restaurant. This restaurant is not only a place for dining but also a place for selfies due to instagrammable place design, that innovatively attract customers. Methods used this research is quantitative research that is data gathering through google observation, documentation, and library research. This research method will produce statistic of 100 google review’s writers by using simple random sampling in the form of bar diagram. The purpose of this research is to analyze the positive impact of interior innovation as entrepreneur’s creativity to attract customers. The building is located in highland area of Punclut, therefore customers can witness the beautiful panorama of Bandung City. The restaurant’s design is so unique as to adopt modern style architecture with skyline concept in every corner, such as rainbows with colorful glass wall that can reflect lights and also galaxy like design where the sunlight will penetrate Atlantis buildings that produce dining under the ocean sensations, with auroras, sun, equator, savanas, rainbow alley, and castle gateway. Every corner area has unique and interesting concept, therefore customers can have instagrammable spot to take selfies. Analysis resulting in positive impact of interior innovations in attracting customers. This means the better the interior design the better the customer’s interest in visiting the restaurant. The conclusion of this research can be used by entrepreneurs as innovation reference in culinary business and design in the purpose of creating customers’ satisfaction.